A study on the consumers' attitude towards counterfeit products in Tacloban City an assessment of its market acceptability - Maglalang, Janice M.; Nicer, John Michael B.; Reoma, John Dio Rufino Z. (2010)
The counterfeiting phenomenon has already penetrated the global economy, likewise in the Philippines. And the world has seen and felt the damage it carries to the consumers themselves, the manufacturers of genuine items and the government. Thus, this study attempts to identify the social and personality factors affecting consumer's attitude towards counterfeit products, to assess its relationship and to determine which of those identified factors is dominant in consumers of Tacloban City, the research locale. The outcome will eventually be used as a guide in setting up refined and effective marketing strategies to the manufacturers of genuine products.